Pengaruh Corporate Governance Dan Kinerja Lingkungan Terhadap Kinerja Perusahaan (Studi Pada Perusahaan Manufaktur Peserta Proper 2012-2018) - Herbekti Riyandhono; Rohmawati Kusumaningtias (Universitas Negeri Surabaya, 2021)
Money is the key of football. Football is not only a sport but has turned into an industry. All over Europe, many football clubs have implemented development strategies and made substantial investments to maximize their profits, one of them by listing on the capital market. In the capital market stock prices are very fluctuation. The purpose of this research is observe about the factors that affect stock prices of European football clubs for the period 2016 to 2019 by looking at the influence of financial performance consists of ROI (Return on Investmen), ROE ( Return of Equity), and DAR (Debt to Asset Ratio). Sampling technique using puposive sampling of 9 European football clubs that are active on the stock exchange. Data analysis techniques using multiple linier regression. The results showed that financial peformance of the football clubs affect the stock prices. From the result of the T-test concluded that partially Debt to Asset Ratio has a negative effect on the stock prices, while Return on Investmen and Return of Equity has no significant effect on stock prices. At the end of research the author concluded that the stock prices of a football club is not only determined by the financial performance of the club, but is also influenced by the achievements in the match and fanaticism of supporters